Correlation between alkaline phosphatase, g-glutamyl transpeptidase, and bilirubin with interleukin-1b level in dogs with obstructive jaundice - Nurcahya Setyawan; Vicky S. Budipramana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Surgical management in obstructive jaundice still contributes to significant morbidity and mortality. One of complications following surgery in obstructive jaundice is sepsis. This complication is caused by the toxic effects of bilirubin and bile salts, endotoxins, bacterial translocation, modulation of the immune-inflammatory cascade, decreased cellular immunity and/or nutritional status. Many studies have shown the elevated inflammatory response indicator, interleukin-1 (IL-1b), in patients with obstructive jaundice. However, only a few report described the association between the indicators of obstructive jaundice (alkaline phosphatase [ALP], g-glutamyl transpeptidase [GGT], and bilirubin)and the indicator of inflammatory response (interleukin-1b [IL-1b]). This study aimed to investigate the association between the indicator of obstructive jaundice (ALP, GGT, and bilirubin) and the level of interleukin-1b (IL-1b) in dogs as the animal model. We performed ligation on distal common bile ducts (CBD) to produce a model of obstructive jaundice. Every three days within a month, the blood samples from ten dogs were extracted to determine the ALP, GGT, direct and total bilirubin, and IL-1b levels. We found a significant correlation between the ALP and GGT with IL-1b level with p-value of 0.036 (r=0.626) and 0.003 (r=0.826). However, there was no association between the increased directbilirubin with the IL-1b level (p=0.068; r=0.537). Moreover, the increased level of ALP and GGT had a strong correlation with the increased level of direct bilirubin with p-value of 0.004 (r=0.810) and p=0.011 (r=0.746). In conclusion, the increased level of GGT was the strongest indicator for inflammatory response in dogs with obstructive jaundice. Furthermore, the increased levels of GGT and ALP might imply the development of obstructive jaundice in dogs.